PENGARUH UMUR, GENDER, KEAKTIFAN, EXPERTISE FINANCE DAN MASA JABATAN KOMITE AUDIT TERHADAP MANAJEMEN LABA - Christopher Reynaldi; Hendra Wijaya; Adi Susanto (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2024)
Financial report information is a basic reference for making investment decisions for investors and shareholders. The profit achieved by a company is often a measure in assessing a company's performance. This shows that the existence of profits in financial statements is very important so that supervision over its presentation is needed to avoid earnings management behavior by management, which can obscure financial information to make it less appropriate to current developments. One effort that can be made is to make changes in the management of business entities by having an audit sub-organization division or known as an audit committee as part of improving company control. In this research, testing the existence of an audit committee focuses more on the personal characteristics of each member. In this research, testing the existence of an audit committee focuses more on the personal characteristics of each member. The aim of this research is to examine and analyze the influence of the factors age, sex or gender, level of activity, experience in financial expertise and the general term of office of the audit committee on earnings management. This quantitative research used eighty-five samples of manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The research sample was determined using a purposive sampling technique with reference to certain criteria. The data analysis technique used is multiple linear regression. The results of this study show that the age of the audit committee has a negative effect on earnings management, while the gender of the audit committee, the level of activity of the audit committee, understanding of the audit committee's financial expertise and the age of the audit committee's term of office have no effect on earnings management.